"Wrap healthy snacks with cool packaging" - A qualitative study of mothers' portion size strategies for their children. (1st April 2020) - Tang, Tang; Wang, Wenmeng; Croden, Fiona; Vazirian, Marjan; Hetherington, Marion M.
Abstract: Offering large portions of high energy dense (HED) foods increases overall energy intake in children, a potentially important contributing factor to childhood overweight and obesity. Packaging offers a simple heuristic to encourage healthy eating for nutrient dense foods and to downsize portions of HED foods. However, it is not clear how parents use packaging for portion control, nor how packaging might be used as a solution to offset large portions. Therefore, the aim of the present study was to investigate mothers' portion strategies and how they use packaging to facilitate portion control for children. 21 mothers of 25 children aged 1–5 years participated in semi-structured interviews to identify strategies used by mothers for portioning snack and meal items. Mothers reported feeling confident in amounts offered to their children, and were unaware of, or did not apply, recommendations for age-appropriate portions of meal items and snacks. Mothers portioned according to child appetite, needs and characteristics, not necessarily age. They reported that their child was able to determine for themselves how much to consume. However, mothers also applied restrictions to some foods. No differences in considerations and strategies were found between different ethnic groups of British and Chinese mothers. Mothers reported that packaging was an important determinant of preferences and a useful, convenient means of portion control. To promote appropriate consumption norms in children, a packaging design concept is described to aid downsizing for a highly liked HED food. Future studies should examine how creative packaging solutions influence parents' feeding practices and how this might influence dietary quality through user testing.